ANTECEDENTS OF DHARMA SHASTRAS AND LEGAL PSYCHOLOGY IN DEFINING THE EFFICIENCY OF ADMINISTRATION IN HUMAN RESOURCE MANAGEMENT WORKFORCE CULTURE IN GLOBAL COMPANIES (Lex localis - Journal of Local Self-Government, 2025)
To implement The various Dharma shastras, the law amendment based on ethics and morals value of human resource management systems, human culture and professional ethics of the People, there is no attention given to The methods and procedure in handling the basic structure of human resource management and the limitations regardless to country’s culture and traditions variations between people in global companies , which needs to be addressed. This study investigated the role of the psychology of people in resolving culture bias in human resource management methodology adopted by western countries and how the efficiency of work force culture can further be improved by implementing dharma shastra strategy in to it. The investigation needs to be carried out on how implementing different dharma shastras ethic principles can help in avoiding the cultural bias and conflicts between global companies where people differ from ethnicity, culture, race, and traditions.